THE IMPLEMENTATION OF VISUAL PRINTED MEDIA IN ENGLISH LANGUAGE TEACHING - Regina Rahmi (English Education Department, 2014)
This study which was conducted at SD Islam Laboratorium Neuhen, Mesjid Raya is intended to figure out how the implementation of visual printed media in English language teaching to the six levels. The study was conducted case study research design. The population was 44 and the sample was taken by using nonprobability sample that is convenience sampling was 22 students and 1 English teacher. The research problems are: (1) what kinds of visual printed media are used by the teacher in teaching English? (2) how does the teacher implement visual printed media in teaching English? (3) what are the obstacles faced by the teacher in teaching English by using visual printed media The data were collected by using instruments, namely: observation checklist sheets, interview guidelines, and documentations. Based on the data analysis, it was found that (1) the English teacher at SD Islam Laboratorium used book, magazine and newspaper as printed media. (2) the teacher did three phases in using visual printed media. They are: (a) preparation; learning curriculum and syllabus, the teacher matches the basic competences with appropriate visual printed media, preparing the visual printed media, bring the media to the class, recognizing the types of the students (b) core activity; students’ question about media, student-centered in learning process while using media, good interaction in using visual printed media, cognitive-affective-psychomotor of the student in using visual printed media (c) closing; summarization of using visual printed media, motivation/moral value of using visual printed media, giving homework. In addition the teacher did positive performance in using visual printed media (3) some difficulties faced by the teacher in the implementation of visual printed media in English language teaching, they are: designing lesson plan and preparing appropriate teaching materials as visual printed media. So, it is suggested that English teacher should use the visual printed media, because they are the effective tools in English teaching-learning process.